The Relationship between Job Satisfaction and Organizational Commitment: Case Study of Employees in PT X - Karina Yoveline (iBuss Management, 2015)
Human resource management plays a vital role in a company as it could affect company’s performance. In the last decade, companies are faced with high turnover of Generation Y or Millennial Generation. PT X as a manufacturing company that relies on human capital heavily is in a tight competition with other company. This research is done for the purpose to see whether job satisfaction really has significant correlation with organizational commitment, which may reduce the number of turnover. Data was gathered using simple random sampling by distributing questionnaires to 138 employees in PT X. It was then analyzed by using multiple linear regression. The result shows that the job satisfaction simultaneously has significant correlation with organizational commitment. Meanwhile, as individual dimensions, all but fringe benefit has significant correlation with organizational commitment.Keywords: human resource management, job satisfaction, organizational commitment.